Learn more about

Refine search

Results (displaying matches 1-50 of 56695)  Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
336.a.172032.1 336.a \(y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56\) $G_{3,3}$ 0
400.a.409600.1 400.a \(y^2 = x^6 + 4x^4 + 4x^2 + 1\) $E_1$ 0
574.a.293888.1 574.a \(y^2 + (x^2 + x)y = x^5 - x^4 - 3x^2 + x + 1\) $\mathrm{USp}(4)$ 0
576.b.147456.1 576.b \(y^2 = x^6 + 2x^4 + 2x^2 + 1\) $E_1$ 0
600.b.450000.1 600.b \(y^2 + (x^3 + x)y = -5x^4 + 25x^2 - 45\) $G_{3,3}$ 0
644.a.659456.1 644.a \(y^2 + (x^2 + x)y = -3x^6 - 13x^5 + 4x^4 + 51x^3 + 4x^2 - 13x - 3\) $G_{3,3}$ 0
672.a.172032.1 672.a \(y^2 + (x^3 + x)y = -x^6 - 16x^4 - 75x^2 + 56\) $G_{3,3}$ 0
676.a.562432.1 676.a \(y^2 + (x^3 + 1)y = 2x^5 + 2x^4 + 4x^3 + 2x^2 + 2x\) $G_{3,3}$ 0
688.a.704512.1 688.a \(y^2 = 2x^5 + 4x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
688.a.704512.2 688.a \(y^2 = 2x^5 - 7x^4 - 8x^3 + 2x^2 + 4x + 1\) $\mathrm{USp}(4)$ 0
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
720.b.116640.1 720.b \(y^2 + (x^3 + x)y = -6x^4 + 39x^2 - 90\) $G_{3,3}$ 0
784.c.614656.1 784.c \(y^2 = x^5 - 4x^4 - 13x^3 - 9x^2 - x\) $E_3$ 0
800.a.409600.1 800.a \(y^2 = x^6 - 2x^2 + 1\) $G_{3,3}$ 0
810.a.196830.1 810.a \(y^2 + (x + 1)y = x^5 + 15x^4 + 20x^3 - 297x^2 + 94x - 8\) $N(G_{1,3})$ 0
830.a.830000.1 830.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 16x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ 0
847.d.456533.1 847.d \(y^2 + y = -x^6 - 9x^5 - 22x^4 + 3x^3 + 37x^2 - 24x + 4\) $G_{3,3}$ 0
864.a.221184.1 864.a \(y^2 + x^3y = x^5 - 4x^4 - 6x^3 + 33x^2 - 36x + 12\) $N(G_{1,3})$ 0
864.a.442368.1 864.a \(y^2 = x^6 - 4x^4 + 6x^2 - 3\) $N(G_{1,3})$ 0
880.a.225280.1 880.a \(y^2 = x^5 + 13x^4 + 55x^3 + 76x^2 - 44\) $G_{3,3}$ 0
882.a.302526.1 882.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 5x^3 + 11x^2 - 12x + 5\) $G_{3,3}$ 0
960.a.245760.1 960.a \(y^2 = 2x^5 + x^4 + 4x^3 + x^2 + 2x\) $G_{3,3}$ 0
960.a.368640.1 960.a \(y^2 = x^5 + 13x^4 + 44x^3 + 13x^2 + x\) $G_{3,3}$ 0
960.a.983040.1 960.a \(y^2 = x^5 - 2x^4 - x^3 - 2x^2 + x\) $G_{3,3}$ 0
961.a.923521.1 961.a \(y^2 + (x^3 + x^2 + 1)y = -5x^4 + 4x^3 + 3x^2 - 2x - 3\) $G_{3,3}$ 0
966.a.834624.1 966.a \(y^2 + (x^2 + x)y = x^5 - x^4 + x^3 + x^2 - x + 1\) $\mathrm{USp}(4)$ 0
968.a.234256.1 968.a \(y^2 + x^3y = 6x^4 + 47x^2 + 121\) $G_{3,3}$ 1
976.a.999424.1 976.a \(y^2 + (x + 1)y = x^6 - 2x^5 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 0
980.a.878080.1 980.a \(y^2 + (x^3 + 1)y = -x^6 + x^5 - 4x^4 + 2x^3 - 4x^2 + x - 1\) $G_{3,3}$ 0
990.a.240570.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 28x^4 + 72x^3 + 28x^2 + 3x\) $G_{3,3}$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1083.b.390963.1 1083.b \(y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6\) $G_{3,3}$ 0
1104.b.141312.1 1104.b \(y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46\) $G_{3,3}$ 0
1116.a.214272.1 1116.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
1125.a.151875.1 1125.a \(y^2 + xy = 15x^5 + 50x^4 + 55x^3 + 22x^2 + 3x\) $G_{3,3}$ 0
1136.a.290816.1 1136.a \(y^2 + (x^3 + x^2)y = -5x^4 - 9x^3 + 25x^2 + 40x - 24\) $\mathrm{USp}(4)$ 0
1145.a.143125.1 1145.a \(y^2 + (x^3 + x^2 + x)y = 2x^4 + 4x^3 + 9x^2 + 10x + 9\) $\mathrm{USp}(4)$ 1
1152.a.147456.1 1152.a \(y^2 = x^6 - 2x^4 + 2x^2 - 1\) $J(E_1)$ 0
1164.b.670464.1 1164.b \(y^2 + (x^2 + x + 1)y = 2x^5 - 2x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 0
1184.a.606208.1 1184.a \(y^2 = 2x^5 + x^4 - 8x^3 - 8x^2 - 2x\) $\mathrm{USp}(4)$ 0
1184.a.606208.2 1184.a \(y^2 = x^6 - 2x^5 + 5x^4 - 4x^3 + 6x^2 - 2x + 2\) $\mathrm{USp}(4)$ 0
1197.a.410571.1 1197.a \(y^2 + (x^2 + 1)y = x^5 + 12x^4 - 7x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 0
1200.a.450000.1 1200.a \(y^2 + (x^3 + x)y = 4x^4 + 25x^2 + 45\) $G_{3,3}$ 0
1269.b.102789.1 1269.b \(y^2 + (x^3 + x)y = -2x^6 - x^5 - 21x^4 - 8x^3 - 80x^2 - 16x - 103\) $\mathrm{USp}(4)$ 0
1269.b.102789.2 1269.b \(y^2 + xy = x^5 - x^4 + x^2 + x\) $\mathrm{USp}(4)$ 0
1270.a.325120.1 1270.a \(y^2 + (x^2 + x)y = x^5 + 17x^4 + 76x^3 + 14x^2 - 32x + 3\) $\mathrm{USp}(4)$ 0
1272.a.122112.1 1272.a \(y^2 + (x^2 + 1)y = 3x^5 + 4x^4 + 2x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1300.a.130000.1 1300.a \(y^2 + (x^3 + x)y = 2x^4 + 9x^2 + 13\) $G_{3,3}$ 1
1311.a.814131.1 1311.a \(y^2 + xy = x^5 + 5x^4 + 5x^3 + 4x^2 + x\) $\mathrm{USp}(4)$ 0
1312.c.671744.1 1312.c \(y^2 + (x + 1)y = x^6 + 4x^5 + 7x^4 + 5x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
Next
Download all search results for